Obedience to the Mahram and Its Role in the Muslim Family: An Islamic Family Law Perspective - Adi Kurniawan; Lina Herlina (Postgraduate Programme of UIN Kiai Haji Achmad Siddiq Jember, 2022)
This research examines the role and influence of compliance with mahram law in Muslim family structures in Indonesia, with a focus on social and religious aspects. Using a qualitative approach, this study involved in-depth interviews and participant observation with Muslim family members from various social and educational backgrounds. Data analysis was carried out through grounded theory to identify themes and patterns related to the implementation and perception of mahram law. The research results show that compliance with mahram laws significantly influences family dynamics and religious identity, and reflects deep social values. The study also found friction between traditional and modern values, especially among the younger generation, who are calling for a more flexible interpretation of mahram laws in a changing social context. This research suggests the need for intergenerational dialogue and policy adaptation to bridge differences in interpretation and ensure that mahram law remains relevant to current social conditions.